Metody stymulowania napływu BIZ do Polski przez samorządowe władze lokalne - Mogila, Zbigniew (Methods of Stimulation of FDI inflow to Poland by the Local Self-Government Authorities, 2005)
The purpose of this paper is to present a system of attracting and supporting foreign investors created by the Polish self-government authorities and to outline the main elements of their strategies. Policy of central authorities gives the framework of foreign investors. It ought to be complemented by appropriate activities at the local level. The main instrument is modifying the structure of income and expenditure to create a favourable climate for FDI. It is and will be supported by EU funds as well as central agencies like PAIiIZ. The basic aspect of regional authorities policy is a strategy, which should consist of three elements: regional promotion, appropriate investor service and after-service. The conducted research suggests the differentiation between urban and rural areas in the context of FDI supporting and the use of the most common means.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (11); 2005; nr 1077, s. 40-47